Knowledge, attitude, practice, and influencing factors among patients with osteonecrosis of the femoral head - Guangnian Liu; Chengqi Huang; Zhitong Zhu; Zijing Weng; Xing Chen; Liming Dong (Scientific Reports)
Abstract Osteonecrosis of the femoral head affects young adults, often requiring THA due to compromised blood supply and hip pain. To assess the knowledge, attitudes, and practices (KAP) regarding avascular necrosis in patients. A cross-sectional study was conducted from May 16 to June 19 at Affiliated Hospital of Zunyi Medical University. A total of 933 patients diagnosed with osteonecrosis of the femoral head were recruited. Demographic data were collected, and KAP was assessed through self-designed questionnaires comprising 11 knowledge items (scored 11–55), 8 attitude items (scored 8–40), and 10 practice items (scored 10–50). A total of 933 valid responses were obtained, with 743 (79.6%) being male. Mean KAP scores were: knowledge 34.54 ± 5.19 (range: 11–55), attitude 29.38 ± 5.10 (range: 8–40), and practice 36.82 ± 8.64 (range: 10–50). Item analysis revealed that patients showed positive attitudes towards treatment compliance (89.4% agreeing with the importance of treatment adherence) but felt anxious about their condition (37.8% reporting high anxiety). Regarding practices, patients demonstrated good medication adherence but lower compliance with rehabilitation exercises and follow-up visits. Significant positive correlations were found: knowledge-attitude (r = 0.485, P < 0.001), knowledge-practice (r = 0.580, P < 0.001), and attitude-practice (r = 0.624, P < 0.001). Structural Equation Modeling indicated direct effects of knowledge on attitude (β = 0.466, P < 0.001) and practice, (β = 0.654, P < 0.001), with knowledge also affecting practice indirectly through attitude (β = 0.066, P < 0.001). Patients showed inadequate knowledge but positive attitudes and proactive practices regarding avascular necrosis.